2015
DOI: 10.1103/physrevd.91.024014
|View full text |Cite
|
Sign up to set email alerts
|

Late-time quantum backreaction from inflationary fluctuations of a nonminimally coupled massless scalar

Abstract: We consider the late-time one-loop quantum backreaction from inflationary fluctuations of a nonminimally coupled, massless scalar field. The scalar is assumed to be a spectator field in an inflationary model with a constant principal slow-roll ϵ parameter. We regulate the infrared by matching onto a preinflationary radiation era. We find a large late-time backreaction when the nonminimal coupling ξ is negative (in which case the scalar exhibits a negative mass term during inflation). The one-loop quantum backr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 47 publications
(89 reference statements)
2
33
0
Order By: Relevance
“…This idea goes back a while ago to [23,24] where it was noted that quantum fluctuations of a very light scalar could provide a CC-like contribution to the Friedmann equations. In recent years, similar ideas were examined [25][26][27][28][29][30]. Most recently in [30] it was shown that, for certain ranges of model parameters, the backreaction remains small throughout the expansion of the Universe, and becomes relevant only at late times in matter era where it behaves approximately like a cosmological constant.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This idea goes back a while ago to [23,24] where it was noted that quantum fluctuations of a very light scalar could provide a CC-like contribution to the Friedmann equations. In recent years, similar ideas were examined [25][26][27][28][29][30]. Most recently in [30] it was shown that, for certain ranges of model parameters, the backreaction remains small throughout the expansion of the Universe, and becomes relevant only at late times in matter era where it behaves approximately like a cosmological constant.…”
Section: Introductionmentioning
confidence: 95%
“…The dominant contribution to the light scalar field correlators in inflation comes from the superhorizon modes (of wavelengths k > 1/aH). This is also true for the very light or massless scalar fields in subsequent evolution of the Universe, namely during radiation and matter periods [28,30]. The slow-roll approximation usually employed to derive the stochastic equations need not be correct in situations when the scalar becomes very massive, meaning m H. Since during decelerating periods of expansion the Hubble rate decays, this can eventually become true.…”
Section: Stochastic Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…From now on we will only consider situations where (3.5) is satisfied and this is required for the validity of the derivation in [12,63]. Situations where this restriction cannot be imposed can also be approached analytically, see for example the works [54,64,65] Following [12] we will first introduce a physical UV cut-off as…”
Section: Calculating φ 2mentioning
confidence: 99%
“…In the following, we use WKB approximation to achieve a UV expansion for the mode functions. 17,18 Since a basis of solutions for large k is given by {e −ikη , e ikη }, which are normalized by the Wronskian, thus the full positive frequency solutions of the mode equation (2.18) can be written as a…”
Section: Flrw Background and Field Equationsmentioning
confidence: 99%